MODEL PROBLEM POSING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BAHASA INGGRIS DI PRODI DESAIN INTERIOR TAHUN 2018 - Etty Ekowati (Institut Seni Indonesia Surakarta, 2019)
Classroom Action Research (CAR) is a way for lecturers to improve and evaluate classroom learning. With CAR, lecturers can find out problems in the teaching and learning process in the classroom. English course is a subject that must be taken by design students. To overcome the problems in learning English the problem posing model is used. Problem posing, namely problem solving through elaboration, which is to reformulate the problem into parts that are simpler so that it is understood. The syntax is: understanding, solutions, identifying errors, minimizing writing counts, looking for alternatives, compiling questions. The formulation of the problem in this research is how the technique of applying English subject learning with the probem posing model in Interior Design Study Program students at ISI Surakarta and whether the application of the problem posing learning model through English subjects can improve verbal skills in Interior Design Study Program students at ISI Surakarta. The research objectives in this study are to describe the application techniques of learning English courses with probem posing models in Interior Design Study Program students at ISI Surakarta and explain the application of problem posing learning models through English subjects that can improve verbal skills in Interior Design Study Program students at ISI Surakarta This type of research is classroom action research. The results of this study are to find techniques for applying English learning courses with the probem posing model in Interior Design Study Program students at ISI Surakarta and explain the application of the probem posing learning models through English courses that can improve verbal abilities in Interior Design Study Program students at ISI Surakarta. Keywords: CAR, Problem posing, evaluation, model